Impact of bioinoculants on seed germination, early growth and rhizospheric microbial community of Moringa oleifera L. - Jaydeep, P; Monalisa, S P; Chakradhar, P; Chiranjeevi, K; Sahil, S; Dev, N Y (Plant Science Today, 2026)
An experimental study was conducted under the supervision of the Department of Silviculture and Agroforestry, College of Horticulture and Forestry, ANDUAT University, Uttar Pradesh, to assess the Impact of bioinoculants on seed germination, early growth and rhizospheric microbial community of Moringa oleifera L. The duration of the experiment lasts for one season. In this the seeds were initially germinated under laboratory conditions and later transferred to polybags in a nursery setting. The study explored the effects of both individual and combined applications of microbial bioinoculants such as Azotobacter (10 mL), Pseudomonas (10 mL) and seaweed (5 mL) extract using a Completely Randomized Design (CRD) for germination and Randomised Block design (RBD) for growth and microbial count with 3 replications. Results revealed that integrated treatments significantly outperformed individual applications and the control group across several germination and vigour-related parameters. Notable improvements were observed in emergence rate (85.93 %), germination percentage (88.66 %), mean germination time (lowest 5.66 days), speed of germination (4.5), mean germination rate (0.216), mean daily germination (0.833), peak value (1.6), germination value (30.42), seedling vigour (87.96) and overall germination efficiency along with growth and enhanced microbial community (Azotobacter- 9.397 × 106 and Pseudomonas spp.- 9.297 × 105). The best-performing combination of Azotobacter + Pseudomonas + Seaweed (T7) displayed enhanced seed vigour and superior morphological traits such as greater plant height (52.5 cm), stem thickness (5.86 mm) and biomass accumulation (fresh 23.91 g and dry weight 6.46 g of plants) and increased microbial population (Bacteria- 13.797 × 105, Actinomycetes- 10.799 × 106, Fungi-7.847 × 104). The synergistic effect of combined bioinoculants suggests a strengthened microbial interaction that enhances nutrient availability, hormonal stimulation and root microbe signalling. These findings underscore the potential of integrated bio stimulant strategies for boosting early-stage development of Moringa oleifera, offering a promising, sustainable approach for improving nursery practices and promoting eco-friendly agroforestry interventions.